2013
DOI: 10.1007/s00253-013-5351-6
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and diagnostic use of a novel recombinant single-chain antibody against rabies virus glycoprotein

Abstract: Rabies virus (RABV) causes a fatal infectious disease, but effective protection may be achieved with the use of rabies immunoglobulin and a rabies vaccine. Virus-neutralizing antibodies (VNA), which play an important role in the prevention of rabies, are commonly evaluated by the RABV neutralizing test. For determining serum VNA levels or virus titers during the RABV vaccine manufacturing process, reliability of the assay method is highly important and mainly dependent on the diagnostic antibody. Most diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…DNA aptamers for the purification of Influenza A viruses displayed a K a in the order of 10 7 M ‐1 ) or the results are obtained using the virus protein and not the whole virus as the target (e.g. an antibody with affinity towards a rabies virus glycoprotein displayed a K a of 10 6 M ‐1 ). The maximum capacity of the support is not usually determined for virus purification schemes which does not allow a fair comparison with the current work.…”
Section: Resultsmentioning
confidence: 99%
“…DNA aptamers for the purification of Influenza A viruses displayed a K a in the order of 10 7 M ‐1 ) or the results are obtained using the virus protein and not the whole virus as the target (e.g. an antibody with affinity towards a rabies virus glycoprotein displayed a K a of 10 6 M ‐1 ). The maximum capacity of the support is not usually determined for virus purification schemes which does not allow a fair comparison with the current work.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we developed a new mAb that reacts specifically with the RABV P protein and confirmed its applicability to the RFFIT. Numerous previous studies have reported antibodies developed as diagnostic reagents for rabies detection that target the N protein [ 12 , 13 ] or G protein [ 14 , 15 ]. N protein is related to the immune response and pathogenicity in the host.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, most of the commercial antibodies available for rabies diagnosis are designed to detect rabies-related lyssaviruses along with RABV most of the cases [ 25 ]. The majority of diagnostic laboratories utilize commercial reagents [ 26 ], whereas some utilize in-house products [ 15 , 27 , 28 ]. Both polyclonal antibodies and mAbs, which are specific to the entire virus or to the nucleocapsid protein and are conjugated with a fluorophore, can be used for rabies diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Bên cạnh đó, kháng thể đơn chuỗi có thể được 47 sử dụng cho mục đích điều chỉnh và phát hiện sự hoạt động của các protein trong tế bào, như vậy phù hợp cho việc sử dụng làm vaccine (Alvarez-Rueda et al, 2009). Ngoài ra, kháng thể đơn chuỗi còn được ứng dụng trong điều trị ung thư (Chester et al, 2004) và chống lại virus bệnh dại glycoprotein (Yuan et al, 2013).…”
Section: Mở đầUunclassified